Albania - BEEPS-at-a-glance - World Bank (Washington, DC, 2012)
The EBRD-World Bank Business Environment and Enterprise Performance Survey (BEEPS) is a joint initiative of the European Bank for Reconstruction and Development and the World Bank. The BEEPS has been carried out in three rounds in 1999, 2002, and 2005 and covers virtually all of the countries of Central and Eastern Europe and the former Soviet Union, as well as Turkey. (It has not been possible to implement this survey in Turkmenistan.) The BEEPS covers a broad range of issues about the business environment, and this note presents some simple indicators for key areas. This note focuses exclusively on the main BEEPS for 2002 and 2005 and presents simple averages over all firms with non-missing data. Regional aggregates are computed using firm-level data. Many of the apparent changes over time and difference between countries may not be statistically significant.